Reaping the Benefits of Financial Globalization - Dell'Ariccia, Giovanni (Occasional Papers; Occasional Paper ;, 2008)
Financial globalization has increased dramatically over the past three decades, particularly for advanced economies, while emerging market and developing countries experienced more moderate increases. Divergences across countries stem from different capital control regimes, and factors such as institutional quality and domestic financial development. Although, in principle, financial globalization should enhance international risk sharing, reduce macroeconomic volatility, and foster economic growth, in practice its effects are less clear-cut. This paper envisages a gradual and orderly sequencing of external financial liberalization and complementary reforms in macroeconomic policy framework as essential components of a successful liberalization strategy.